Rachel Carson's Silent spring [videorecording (DVD)] - Goodwin, Neil; Chadwick, Alex, 1947-; Streep, Meryl (WGBH Boston Video, 2007)
Witness the life of passionate biologist and environmentalist, Rachel Carson, and how she exposed the effects of the unregulated use of pesticides and herbicides by the federal government, and sparked a revolution in environmental policy.